Honk for Jesus. Save your soul [videorecording (DVD)] - Ebo, Adamma; Hall, Regina; Brown, Sterling K.; Crute, Austin; Conphidance; Rogers, Devere; Barnes, Avis Marie; Beharie, Nicole (Universal, 2022)
Proud first lady of a Southern Baptist megachurch, Trinitie Childs carries immense responsibility on her shoulders. After a scandal involving her husband, the church is forced to temporarily close, leaving Trinitie struggling to manage the aftermath. Now, she and her spouse must rebuild their congregation and reconcile their faith by all means necessary to make the biggest comeback that commodified religion has ever seen.